Where are the children now? [compact disc, unabridged] - Clark, Mary Higgins; Burke, Alafair (Where are the children, 2023)
When we last saw Nancy Harmon, tragedy had struck her family as she suffered through the heartbreak of her first marriage, the ghastly deaths of her two children, hostile media coverage, and the harsh criminal charges against her. Nancy was forced to relocate across the country, change her name and appearance, anything that could be used to identify her controversial past. Years later, after a fresh start on idyllic Cape Cod, Nancy remarried and had two more children, but her worst nightmare resurfaced when they disappeared as well. Now, in the sequel to the book that launched the career of Queen of Suspense Mary Higgins Clark, Nancy Harmon's children are no longer kids, but they are once again in danger in this propulsive mystery.